Analysis of Improving The Efficiency and Effectiveness of State Property (Sp) In The BPS Work Unit of Ambon City - Sujatmiko, Bambang; Zubdatu Zahrati; Farid, Ibnu; Mahawati, Hemi; Mairina, Catur Liliek; Widianto, Ari (Universitas Kristen Cipta Wacana, 2025)
State Property (SP) is an important asset in supporting various government agencies. Good management of SP based on the principles of effectiveness, efficiency, ethics, and economy is the key to ensuring that state resources are used optimally. However, in its implementation, problems often arise that hinder the management of SP, starting from the constraints of the availability of minimal SP maintenance budget, frequent overlapping of authority in the Work Unit, to the lack of order in the management and maintenance of state assets due to various things. This study examines the main principles in the management of SP and the challenges faced by the BPS Ambon City Work Unit in implementing these principles. This study is supported by qualitative methods through interviews, observations, and collection of relevant data to support information in the preparation of this scientific paper. The research conducted ultimately resulted in the reality that in efforts to improve the principles of efficient and effective SP management, there are many obstacles experienced by the Work Unit, but to overcome this, steps are needed that begin with managing the available budget to finance the maintenance of state assets and understanding the procedures for good and orderly SP management, where all of these efforts require the role of the Work Unit Leader as the Authorized User of Goods (KPB)